5
$\begingroup$

Assume a two player symmetric game is given by $n\times n$ payoff matrix $A$ for the row player (and $A^t$ for the column player).

Let $B$ be a matrix such that $\forall i,j\in [n]:B_{i, j}\geq A_{i,j}$.

Assume $a$ is a symmetric equilibrium in $A$, $b$ is a symmetric equilibrium in $B$ and that $a$ and $b$ has the same support.

Does it mean player's payoff under $a$ (playing matrix $A$) can not be larger than the payoff of playing $b$ in game $B$?


Formulating the claim in linear algebra:

Let $A,B\in [0,1]^{n\times n}$ such that $\forall i,j\in [n]:B_{i, j}\geq A_{i,j}$.

Denote by $\Delta $ the set of probability distributions over $[n]$.

Let $a,b\in \Delta$ be two distribution vectors.

Does

  1. $\forall x\in \Delta: x^tAa\leq a^tAa \ \ $ (i.e. $a$ is an equilibrium for $A$)
  2. $\forall x\in \Delta: x^tBb\leq b^tBb \ \ \ $ (i.e. $b$ is an equilibrium for $B$)
  3. $\forall i\in [n]: a_i>0 \iff b_i>0 \ \ $ ($a,b$ have the same support)

Imply $$a^tAa\leq b^tBb?$$

If not, does the answer change if $A,B$ are symmetric?


Notice that without the support condition, the claim is false, for example-

$A= \left( \begin{array}{ccc} 1 & 0 \\ 0 & 0.1 \\ \end{array} \right) $ $B= \left( \begin{array}{ccc} 1 & 0 \\ 0 & 0.5 \\ \end{array} \right) $

$a= \left( \begin{array}{ccc} 1 \\ 0 \\ \end{array} \right) $ $b= \left( \begin{array}{ccc} 0 \\ 1 \\ \end{array} \right) $

$\endgroup$
2
$\begingroup$

For a simple counterexample let $$ A = B = \left( \begin{array}{cc} 1 & 0 \\ 1 & 0 \end{array} \right). $$ In this game any strategy pair will constitute a Nash-equilibrium. Let $$ a^t = \left(\frac{2}{3}, \ \frac{1}{3} \right), b^t = \left(\frac{1}{3}, \ \frac{2}{3} \right). $$ Then the expected payoffs are larger in the symmetric equilibrium associated with $a$.

If you wish for $B$ to be strictly larger than $A$ you can easily modify this example, simply multiply all of $B$'s elements with a number larger than 1 but smaller than 2.

A counterexample where neither $A$ nor $B$ are singular: $$ A = \left( \begin{array}{cc} 4 & 0 \\ 6 & -4 \end{array} \right), \ B = \left( \begin{array}{cc} 4 & 1 \\ 6 & 0 \end{array} \right) $$ $$ a^t = \left(\frac{2}{3}, \ \frac{1}{3} \right), b^t = \left(\frac{1}{3}, \ \frac{2}{3} \right). $$ $$ A \cdot a = \left( \begin{array}{c} \frac{8}{3} \\ \frac{8}{3} \end{array} \right) > \left( \begin{array}{c} 2 \\ 2 \end{array} \right) = B \cdot b $$

$\endgroup$
  • $\begingroup$ Love the non-singular counter example, will be using it for some application soon ! $\endgroup$ – R B Jan 1 '15 at 7:56

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.